Are they too hard on them? : student discipline in charter and regular public schools - Sampson, William A., 1946-; Gulasingam, Nandhini (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
While much of the debate over the growth of charter schools center on the student academic performance of charter schools as well as the financial impact that they have on school budgets, there is a growing concern that charter schools use harsh discipline to nudge certain students out. The concern is that charter schools use excessive discipline not just to bring about order and rigor in schools, but to push students who might cost more to educate or lower test scores to leave charter schools.Given that charter schools, unlike regular public schools, are free to admit or eject whomever they want, there is concern that those schools are not only skimming in admissions, but also pushing out certain kinds of students. While several scholars have raised this concern, there is not much research on this critical topic. The current book changes that. We compare student discipline rates in four major cities among regular and charter schools to determine whether charter schools are more likely than regular schools to discipline students. We also study the relationships among a host of variables by six different discipline categories.